Migration and social cohesion in the UK / Mary J. Hickman, Nicola Mai and Helen Crowley. - Hickman, Mary J. (Identity studies in the social sciences., 2012)
Based on a flagship research project for the Joseph Rowntree Foundation's Immigration and Inclusion programme, this book argues that social cohesion is achieved through people - both new arrivals and the long-term settled - being able to resolve the conflicts and tensions within their day-to-day lives in ways that they find positive.